2018
DOI: 10.1016/j.ccell.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Loss of CDKN2A Initiates Melanoma Invasion via BRN2 Activation

Abstract: Loss of the CDKN2A tumor suppressor is associated with melanoma metastasis, but the mechanisms connecting the phenomena are unknown. Using CRISPR-Cas9 to engineer a cellular model of melanoma initiation from primary human melanocytes, we discovered that a lineage-restricted transcription factor, BRN2, is downstream of CDKN2A and directly regulated by E2F1. In a cohort of melanocytic tumors that capture distinct progression stages, we observed that CDKN2A loss coincides with both the onset of invasive behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 70 publications
(103 reference statements)
9
129
0
Order By: Relevance
“…Phase images were analyzed using application specific software modules in the HStudio software. The metastatic 1205Lu line demonstrated significantly increased motility over the nonmetastatic WM793 line with as few as 4 h of imaging, consistent with previous reports (29). 1A) (29).…”
Section: Dhc Analysis Of Proliferation and Motilitysupporting
confidence: 91%
See 1 more Smart Citation
“…Phase images were analyzed using application specific software modules in the HStudio software. The metastatic 1205Lu line demonstrated significantly increased motility over the nonmetastatic WM793 line with as few as 4 h of imaging, consistent with previous reports (29). 1A) (29).…”
Section: Dhc Analysis Of Proliferation and Motilitysupporting
confidence: 91%
“…Previous studies have demonstrated that the WM793 line proliferates more rapidly and is less motile as compared with the 1205Lu line (29). Previous studies have demonstrated that the WM793 line proliferates more rapidly and is less motile as compared with the 1205Lu line (29).…”
Section: Dhc Analysis Of Proliferation and Motilitymentioning
confidence: 99%
“…In contrast, the phenotype of invasive melanoma was associated with multiple aberrations, typically biallelic inactivation of CDKN2A . Functional data corroborate this association, as CDKN2A deletions, engineered into primary human melanocytes, confer migratory, invasive, and metastatic phenotypes (Zeng et al, 2018 [this issue of Cancer Cell ]).…”
Section: Discussionmentioning
confidence: 76%
“…To date, studies on molecular mechanisms of melanoma mainly focus on protein‐coding genes, such as NRAS , MTOR , CDKN2A , and BRAF . However, the initiation and progression of melanoma could not be fully explained by protein‐coding genes .…”
Section: Introductionmentioning
confidence: 99%